(untitled) (Comparative & International Education Series, 2021)
The COVID-19 pandemic has taken the world by storm. On March 18, Malaysia was put into a countrywide lockdown, where all non-essential businesses have to close, including shutting down the campuses of institutions of higher learning. Many institutions have no choice but to go forward quickly with online modes of teaching and learning. Based on an autoethnographic research, it is concluded that private institutions faced financial challenges brought about by students’ decisions to defer and/or delay their studies. The institutions also encounter challenges in the disruptions of their teaching and learning activities, including the internship program. Moving forward, private institutions need to embrace online modes of teaching and learning. Furthermore, faculty members and students should also develop resilience through enhancing their social and cultural capital. How to cite: Lim, B. (2022). Coronavirus disruptions to the private higher education sector in Malaysia In J. S. McKeown, K. Bista, & R. Y. Chan (Eds.), Global higher education during COVID-19: Policy, society, and technology (pp. 92-103). STAR Scholars. https://starscholars.org/product/global-education/